Knowledge on Infection Prevention and Control and associated factors among undergraduate health professional students at Makerere University College of Health Sciences, Uganda. - Racheal Nalunkuma (Public Library of Science (PLoS), 2021)
Introduction To practice adequate Infection Prevention and Control (IPC) measures, health professional students need to have adequate knowledge of IPC. In this study, we assessed the knowledge of health professional students at Makerere University College of Health Sciences on Infection Prevention and Control. Methods We conducted a cross-sectional online survey among health professional students studying at Makerere University College of Health Sciences located in Kampala, Uganda. An adapted questionnaire was used to measure knowledge on Infection Prevention and Control among students. Results A total of 202 health professional students were included in the study. The mean age was 24.43 years. Majority were male 63.37% (n = 128), from the school of medicine 70.79% (n = 143) and used one source of information for IPC 49.50% (n = 100). Being in year three (Adjusted coefficient, 6.08; 95% CI, 2.04-10.13; p-value = 0.003), year four (Adjusted coefficient, 10.87; 95% CI, 6.91-14.84; p < 0.001) and year five (Adjusted coefficient, 8.61; 95% CI, 4.45-12.78; p < 0.001) were associated with a higher mean in total percentage score of knowledge on IPC compared to being in year one. Conclusion IPC knowledge was good among health professional students in Makerere University although more emphasis is needed to improve on their IPC knowledge in various sections like hand hygiene. Infection Prevention and Control courses can be taught to these students starting from their first year of university education.